Dynamics of particulate organic matter composition in coastal systems: A spatio-temporal study at multi-systems scale. (August 2017) - Liénart, Camilla; Savoye, Nicolas; Bozec, Yann; Breton, Elsa; Conan, Pascal; David, Valérie; Feunteun, Eric; Grangeré, Karine; Kerhervé, Philippe; Lebreton, Benoît; Lefebvre, Sébastien; L'Helguen, Stéphane; et al.
Highlights: Two littoral systems, eight embayments and one estuary were studied. Phytoplankton dominates POM in all systems except in the estuary (terrestrial POM). Mediterranean systems present a non-negligible contribution of diazotroph organisms. POM composition and its seasonality undergo an inshore-offshore gradient. Hydrodynamics and geomorphology likely drive the variability of POM composition. Abstract: In coastal systems, the multiplicity of sources fueling the pool of particulate organic matter (POM) leads to divergent estimations of POM composition. Eleven systems (two littoral systems, eight embayments and semi-enclosed systems and one estuary) distributed along the three maritime façades of France were studied for two to eight years in order to quantify the relative contribution of organic matter sources to the surface-water POM pool in coastal systems. This study was based on carbon and nitrogen elemental and isotopic ratios, used for running mixing models. The POM of the estuary is dominated by terrestrial material (93% on average), whereas the POM of the other systems is dominated by phytoplankton (84% on average). Nevertheless, for the latter systems, the POM composition varies in space, with (1) systems where POM is highly composed of phytoplankton (≥93%), (2) systems characterized by a non-negligible contribution of benthic (8–19%) and/or river (7–19%) POM sources, and (3) the Mediterranean systems characterized by the contribution of diazotroph organisms (ca. 14%). A continent-to-ocean gradient of river and/or benthic POM contribution is observed. Finally, time series reveal (1) seasonal variations of POM composition, (2) differences in seasonality between systems, and (3) an inshore-offshore gradient of seasonality within each system that were sampled at several stations. Spatial and seasonal patterns of POM composition are mainly due to local to regional processes such as hydrodynamics and sedimentary hydrodynamic (e.g. resuspension processes, changes in river flows, wind patterns influencing along-shore currents) but also due to the geomorphology of the systems (depth of the water column, distance to the shore). Future studies investigating the link between these forcings and POM composition would help to better understand the dynamics of POM composition in coastal systems.